Regulation of the DNA Methylation Landscape in Human Somatic Cell Reprogramming by the miR-29 Family - Hysolli, Eriona (Stem Cell Reports, 2016)
Reprogramming to pluripotency after overexpression of OCT4, SOX2, KLF4, and MYC is accompanied by global genomic and epigenomic changes. Histone modification and DNA methylation states in induced pluripotent stem cells (iPSCs) have been shown to be highly similar to embryonic stem cells (ESCs). However, epigenetic differences still exist between iPSCs and ESCs. In particular, aberrant DNA methylation states found in iPSCs are a major concern when using iPSCs in a clinical setting. Thus, it is critical to find factors that regulate DNA methylation states in reprogramming. Here, we found that the miR-29 family is an important epigenetic regulator during human somatic cell reprogramming. Our global DNA methylation and hydroxymethylation analysis shows that DNA demethylation is a major event mediated by miR-29a depletion during early reprogramming, and that iPSCs derived from miR-29a depletion are epigenetically closer to ESCs. Our findings uncover an important miRNA-based approach to generate clinically robust iPSCs.